Implementation of Bandung – Suwon Sister City Cooperation to Improve the Quality of Education in Bandung City - Isna Pauziah Parihah, Neng; Wahyu Nugroho, Bambang (International Journal of Education and Digital Learning (IJEDL), 2024)
Bandung and Suwon sister city cooperation with the primary activity started from the Suwon City Government who wished to set up a city accomplice with Bandung City. The cooperation covers the fields of Economy, Trade, Tourism, Science and Technology Investment, Education, Culture, Welfare, Youth and Sports. However, given the number of areas of cooperation between the two cities and the relatively long period of time, this study identifies the actual results or impact of the implementation of programs that have been carried out in the sister city cooperation between Bandung and Suwon. Focusing on the field of education, this study uses a qualitative field research method to collect and analyze data or the object of the research written. This study found that the sister city cooperation between Bandung and Suwon in the field of education is still not optimized. This is due to the lack of role of the local government in this sister city cooperation to bridge the sister city cooperation program.